2004
DOI: 10.1016/s1534-5807(04)00022-x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Regulates Mammary Gland Development via an Autocrine-Paracrine Loop

Abstract: Mammary gland development is controlled by a dynamic interplay between endocrine hormones and locally produced factors. Biogenic monoamines (serotonin, dopamine, norepinephrine, and others) are an important class of bioregulatory molecules that have not been shown to participate in mammary development. Here we show that mammary glands stimulated by prolactin (PRL) express genes essential for serotonin biosynthesis (tryptophan hydroxylase [TPH] and aromatic amine decarboxylase). TPH mRNA was elevated during pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
247
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(278 citation statements)
references
References 29 publications
(5 reference statements)
14
247
2
3
Order By: Relevance
“…Matsuda et al (2004) reported the discovery of serotonin (5-HT) synthesis in the mammary glands of rodents. Furthermore, they reported that 5-HT (in rodents) acted as a local feedback signal that inhibited lactation.…”
Section: Altered Dry Periodsmentioning
confidence: 99%
“…Matsuda et al (2004) reported the discovery of serotonin (5-HT) synthesis in the mammary glands of rodents. Furthermore, they reported that 5-HT (in rodents) acted as a local feedback signal that inhibited lactation.…”
Section: Altered Dry Periodsmentioning
confidence: 99%
“…Serotonin (5-HT), which acts as both a neurotransmitter and hormone that entrains circadian clocks, has been proposed to be a feedback inhibitor of lactation (Stull et al, 2007). The gene coding for tryptophan hydroxylase 1, the rate-limiting enzyme for serotonin synthesis, is expressed in bovine mammary epithelial cells and is upregulated by prolactin in vitro (Matsuda et al, 2004). Addition of serotonin to mammosphere cultures reduced the expression of a-lactalbumin and casein genes.…”
Section: Plaut and Casey 396mentioning
confidence: 99%
“…In fact, mammary glands stimulated by prolactin (PRL) expressed essential genes for serotonin biosynthesis. Tryptophan hydroxylase mRNA increased during pregnancy and lactation with consequent 5-HT found in mammary gland epithelial cells and in milk (Matsuda et al 2004). Plasma 5-HT, which has a rapid turnover distinct from that of platelet 5-HT, is the fraction which shows the equilibrium state between synthesis by enterochromaffin cells, the inactivation by liver and lung monoamino oxidase (MAO), and platelet uptake.…”
Section: Introductionmentioning
confidence: 99%